Islamic Philanthropy: Implementation of Regulations And Utilization of Waqf Proceeds in Jambi - Maryani; Zainal Arifin; M. Kamal Fathoni; Neni Triana; Pidayan Sasnifa; Shofian Bin Ahmad; Rahmi Hidayati; Ramlah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The management and utilization of waqf is regulated in the waqf law. However, the majority of Nazirs did not carry it out. This was caused by the Nazirs' doubts that the state legal norms governing waqf were not in accordance with Islamic legal norms. This research aims to analyze the application of state legal norms in managing and utilizing waqf assets. The research method uses empirical juridical with a qualitative approach combined with statutory and conceptual approaches. The research location is in East Tanjung Jabung Regency, Jambi. The research results show that Nadir's low knowledge and understanding of state legal norms governing waqf management, including their low experience and professionalism in managing waqf, causes doubts for Nadir in developing management and productive use of waqf. Even though state legal norms governing the management and use of waqf do not conflict with Islamic law, madhab scholars view the use of waqf assets as permissible, although some scholars have differing opinions regarding the limits of such use. Therefore, increasing Nadir's understanding of state legal norms and Islamic legal norms that regulate the management and utilization of waqf is an urgent agenda in order to improve the welfare of the people.